Factor Analysis of Learning Difficulties of SMKN 1 Students in Civic Education Subjects - Unitasari, Mila; Nuryadi, M Hendri; Winarno, Winarno (Jurnal Civicus, 2023)
Low student learning outcome in the subjects of Civic Education if left unchecked can affect the students’ civic skills and attitudes. In theory, this can be categorized as learning difficulties. The purpose of this study is to find out the factors causing the class XI students’ learning difficulties of SMK Negeri 1 Kepil on the civic knowledge component and find out the teachers’ efforts and contraints in increasing the students’ civic knowledge. This research used qualitative methods with a case study approach. Data sources were obtained through observations of teaching and learning activities, Civic Education teacher’s interviews, vice principal interviews, students interviews and analysis of various relevant documents. Furthermore, the results of the study showed that the factors that cause students’ learning difficulties consisted of intelligence, talents, interests, motivation, and peer influences at school and community environment. The efforts made by Civic Education teachers to improve civic knowledge include carrying out observations so that the root of the problem can be revealed. In addition, the teachers provide motivation, used varied learning models and methods, use learning media, and provided reflection. The obstacles that arose in carrying out these efforts came from the teachers themselves, students, and in terms of facilities and infrastructure.